PENGARUH KUALITAS PRODUK DAN CITRA MEREK TERHADAP LOYALITAS KONSUMEN PADA PRODUK OLI FEDERAL DI WILAYAH JAKARTA TIMUR (STUDI KASUS PADA BENGKEL RESMI AHASS 2657 DEWI SARTIKA) - Agung Kresnamurti R.P.; Ariani Putri (Jurnal Ilmiah Econosains, 2012)
Abstract The purpose of this study are: 1)Knowing the description of the product quality, brand image, and consumer loyalty of Federal Oil, 2) Knowing the influence of product quality to consumer loyalty of Federal Oil, 3) Knowing the influence of brand image to consumer loyalty of Federal Oil, 4)Knowing the influence product quality and brand image simultaneously to consumer loyalty of Federal Oil. The unit of observation is 204 respondents who turn of motor oil in Dewi Sartika and use Federal oil consumption four times or more. Research designs used are descriptive and causal. Sample determination technique using convenience sampling. Data collection techniques using a questionnaire with a Likert scale from 1 to 5. The result of this descriptive study is variable of quality product significantly affects consumer loyalty of Federal Oil, variable of brand image significantly affects consumer loyalty of Federal Oil. Results of hypothesis testing through t test and F test shows the influence variable quality of product to the consumer loyalty, the effect of brand image variable to the consumer loyalty. From these studies show that the percentage contribution to the influence of quality of product and brand image to the consumer loyalty by 54.2% (R2). The remaining 45.8% is influenced or explained by other variables not included in this research model. Keywords: Quality of Product, Brand Image, Consumer Loyalty, Federal Oill.